تخلیقِ انسانی اور قرآن کا تصورِ ارتقا:منتخب آرا کامختصر جائزہ (Al-Qamar, 2022)
The biological evolution (based on the natural selection, mutation, and homology) of man is being presented as a process that took place over several stages, culminating in the creation of Adam, Eve, and other human beings. But the Qur’an has indicated them as the finest of all creations and endowed them with the abilities to speak, communicate, think, and make ethical choices, which differentiate them from animals. The purpose of this analytical study is to analyze the concept of the creation of man in perspective of the primary sources of Islamic Shariah (the Quran and Hadith). The creation of man is seen as a central event in the history of the world. The Islamic concept of the creation of man is rooted in the Quranic narratives, which emphasise the unique and special nature of humans, their divine purpose, and their responsibilities towards their Creator and towards each other. But animals don’t lead their lives in such a systematic and responsible way. Someone should deeply analyze the behaviour and obligations of humans and compare them with those of animals before supporting the evolutionary thoughts based on homology.
Keywords: Creation of Man; Quran; Human Evolution; Islam and Evolution; Kinds of Creation of Man